Molecular characterization of Escherichia coli isolates obtained from beef using rapid pulsed-field gel electrophoresis - Ang, Chung Huap. (Universiti Malaysia Sarawak (UNIMAS), 2003)
Rapid pulsed-field gel electrophoresis was used to compare and analyze the genetic relationship among 40 Escherichia coli isolates obtained from local beef, Australia beef and India beef. Among the 40 Escherichia coli isolates used in this study, 8 Escherichia coli isolates obtained from local beef (2 samples) and Australia beef (6 samples) generated distinct pulsed-field gel electrophoresis DNA profiles with 2 to 10 DNA fragments by using restriction endonuclease, Xba I. However, the other 32 Escherichia coli isolates, including all the Escherichia coli ioslates obtained from India beef were untypable due to heavy smearing, thus preventing the generation of DNA profiles. Results obtained in this study showed no genetic similarity among these 8 Escherichia coli isolates as the F values ranged from 0.0000 to 0.3750. F values that lower than 0.90 concluded that these 8 Escherichia coli isolates obtained from both local beef and Australia beef were not genetically related to each other.